Right Heart Failure Atrial Septal Defect (DSA) Secondary With Tricuspid Regurgitation - Doharjo Manullang; Menang B. Tarigan; Salomo G.U. Simanjuntak; Ivonne RVO Situmeang; Evi Rosa Simanjuntak (Indonesian Journal of Chemical Science and Technology (IJCST), 2026)
Congenital heart disease is a structural or functional abnormality of the cardiovascular system that is present at birth, although it can be found later in life. And the prevalence of ASD is around 9.8%. ASD is a condition where damage occurs in the inter-atrial septum, causing a connection between the left and right atrium. ASD is divided into 4 types: secundum type Atrial Septal Defect, primum type Atrial Septal Defect, sinus venosus type Atrial Septal Defect, and finally coronary sinus type Atrial Septal Defect. Secundum Atrial Septal Defect is the most common type. And generally, more often occurs in women than men with a ratio of 2:1. And the examination modalities in establishing Atrial Septal Defect include Chest X-ray, Electrocardiography and Echocardiography. The following is a case report of a 41-year-old man diagnosed with Secundum Atrial Septal Defect (ASD) + TR. This patient was diagnosed at the age of 41. In its natural course, ASD will cause pulmonary artery pressure to increase with age. ASD closure before age 24 can reduce the risk of long-term mortality to the same level as the ASD-free population. This case study aims to provide insight into diagnosis, management, and patient education to achieve optimal therapy and quality of life.